2012
DOI: 10.1093/ndt/gfs151
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of life in patients with chronic kidney disease: influence of acceptance and personality

Abstract: Acceptance is an important positive variable in accounting for HQL, however, clinicians must be aware that if patients have a high level of neuroticism they are likely to have more difficulties with this coping strategy. These results provide a better understanding of psychological determinants of HQL in CKD, which can initiate another approach of these patients by nephrologists, specific psychological interventions, or other supporting public health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 57 publications
7
62
2
6
Order By: Relevance
“…In the current study, evaluation of the difference between the group with respect to each domain using independent sample "t" test, it is found that there was a significant improvement in the mean domain score in the intervention group for all the four domains as compared to the group that was not provided with an intervention. This observation is in agreement with similar results obtained at other centers using a variety of QoL questioners [15][16][17][18][19][20]. A significant mean score difference (P < 0.01) is indicative that pharmacists' counseling has an impact on improving the QoL in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, evaluation of the difference between the group with respect to each domain using independent sample "t" test, it is found that there was a significant improvement in the mean domain score in the intervention group for all the four domains as compared to the group that was not provided with an intervention. This observation is in agreement with similar results obtained at other centers using a variety of QoL questioners [15][16][17][18][19][20]. A significant mean score difference (P < 0.01) is indicative that pharmacists' counseling has an impact on improving the QoL in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, it is assumed that mental disorders such as anxiety disorders and depression are mostly correlated with the severity of the disease pre-transplant and the occurrence of complications. However, some studies show that the acceptance of the disease is more predictive for a good or bad QoL than the severity of the disease [13,32] .…”
Section: Ters Scl-90-r Sf-36mentioning
confidence: 99%
“…Poppe et al [32] Improving quality of life in patients Åberg et al [33] Cost of a quality-adjusted life year in liver transplantation: The influence of the indication and the model for endstage liver disease score…”
Section: Ters Scl-90-r Sf-36mentioning
confidence: 99%
“…Renal replacement therapies, such as hemodialysis, partially rectify the symptoms experienced by patients and result in additional changes to their lifestyle, which can affect quality of life. (5) The objective of this study is to assess the quality of life related to the health of chronic renal failure patients on dialysis.…”
Section: Introductionmentioning
confidence: 99%